A CRITICAL STUDY OF THE DOMINANT PARADIGM OF ENTREPRENEURSHIP IN THE EMPOWERMENT PROGRAM FOR FORMER WOMEN MIGRANTS - Susanti, Lina Rintis; Sinaga, Hariati (EGALITA, 2025)
AbstractThis study attempts to answer the question of why the programs provided by the government for post-migrant women after they have completed migration (post-migration) seem to be lip service. Rather than empowering and providing protection from various vulnerabilities, the empowerment framework with such characteristics actually burdens women. This study uses a qualitative method with a feminist perspective. The case study approach was chosen in this study in order to illustrate the problem. The case study was taken from the experience in Krasak Village, Indramayu Regency. In looking at the problem of the reduction of empowerment programs for women-returnee, this paper uses the capability perspective of Martha Nussbaum and the intersectionality framework of Patricia Hill Collins. Based on the perspective of capability theory, empowerment should also aim to achieve equality, including targeting the gap in opportunities that are rooted deep in their life cycle in the past. The absence of social support and an enabling environment for a person's growth and development is also recognized as the issue of social inequality that needs to be targeted, in order to achieve equality of conditions for returnee. Meanwhile, based on the intersectionality framework, this study reveals the incompleteness of the approach used in the entrepreneurship program. It has ignored the various vulnerabilities experienced by returnee, which occur as a result of the interaction of several intertwined power systems (gender, class, and development inequality in the areas of origin of returnees) Keywords: Emancipatory empowerment; Women-migrant-returnees; Post-migration vulnerability; Women’s capability gap.AbstrakPenelitian ini berupaya menjawab persoalan mengapa program yang disediakan pemerintah bagi perempuan purna migran setelah mereka selesai bermigrasi (pasca-migrasi) seolah nampak bagai lip service. Alih-alih memberdayakan dan memberikan perlindungan dari berbagai kerentanan, kerangka pemberdayaan yang berkarakterisitik demikian justru membebani perempuan. Penelitian ini menggunakan metode kualitatif dengan perspektif feminis. Pendekatan studi kasus dipilih dalam studi ini dalam rangka untuk mengilustrasikan permasalahan. Studi kasus diambil dari pengalaman di desa Krasak, Kabupaten Indramayu. Dalam melihat persoalan direduksinya program perlindungan dan pemberdayaan perempuan pasca-migrasi, tulisan ini menggunakan perspektif kapabilitas dari Martha Nussbaum dan kerangka interseksionalitas Patricia Hill Collins. Berdasarkan perspektif teori kapabilitas, dalam melakukan pemberdayaan seharusnya juga bertujuan untuk mencapai kesetaraan, termasuk juga menyasar kesenjangan kesempatan yang berakar jauh sejak dari siklus hidup mereka di masa lalu. Absennya dukungan sosial serta enabling environment bagi tumbuh kembang seseorang, juga termasuk dalam persoalan ketimpangan sosial yang penting disasar dalam rangka mencapai kesetaraan kondisi perempuan purna migran. Sementara berdasarkan kerangka interseksionalitas, studi ini mengungkap ketidaklengkapan pendekatan yang digunakan dalam program kewirausahaan karena telah mengabaikan berbagai kerentanan yang dialami perempuan purna migran, yang terjadi sebagai hasil interaksi dari beberapa sistem kuasa yang saling berkelindan (gender, kelas, dan ketimpangan pembangunan di daerah asal purna migran). Kata Kunci: Pemberdayaan emansipatif; Perempuan-purna-migran; Kerentanan pasca-migrasi; Kesenjangan kapabilitas perempuan.